Microfinance dan Pemberdayaan: Suatu Upaya Penanganan Kemiskinan yang Berkelanjutan - Aryo, Bagus (Jurnal Ilmu Kesejahteraan Sosial, 2010)
This study is aimed to answer the challenges faced by the microfinance sector in Indonesia in regards to poverty reduction. Besides economic deprivation, deprivation to access to economic activities such as isolation from reproduction of social capital, social network, family, and business network, are faced by the poor. Microfinance could be utilized as a tool to reduce poverty through social and financial intermediation process within. This study presented a case study of LKM Kube Sejahtera in Sleman, Yogyakarta that transformed the poor to become micro-entrepreneur through the financial and social intermediation process. The first process was a character building process to increase the community's capabilities to be micro-entrepreneurs. Next, in small groups, the financial intermediation process was provided through provisions of loans. In conjunction with this, the social intermediation process was implemented in a sustainable manner where community development worker provides skill building activities such as bookkeeping and marketing social empowerment was initiated through saving initiatives and strengthening network within the groups or with other groups.